Interaction of α- and δβ0-thalassaemia: haematological features and globin chain synthesis analysis. Issue 1 (February 1981) - Galanello, R; Furbetta, M; Melis, M A; Rosatelli, C; Cao, A
Abstract : An observation of suspected interaction of δβ 0 - and α-thalassaemia, identified through careful examination of the family, is reported. The δβ 0 -thalassaemia was of the usual type found in Sardinia, characterised by high Hb F levels and very low levels of glycine in the isolated γCB3 peptide. The haematological findings in the double δβ 0 -/α-thalassaemia heterozygotes were: normal MCV and Hb A2 levels, increased Hb F (11·3 to 16·8%) heterogeneously distributed in red cells, and almost balanced α/β globin chain synthesis ratios.